Turnover intention and the moderating role of career shocks an empirical study of medical staff in public hospitals in Guangzhou, China - Yang, Fan; Duarte, Henrique; Chen, Jianping; Zu, Chenxi (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore how Leader-Member Exchange (LMX), Job Embeddedness (JE), Job Satisfaction (JS), and Career shocks (CS) affect hospital staff’s turnover intention. By offering theoretical and practical insights, it reassures the reader of the study’s value in curbing employee departures and building a more stable workforce.MethodsUsing a longitudinal design and self-administered questionnaires, data were collected in two rounds from 500 medical staff in 12 tertiary public hospitals in Guangzhou, China, between May and September 2023. The data were analyzed with SPSS 26 and PROCESS macro for SPSS 4.1, including descriptive statistics, correlation analysis, and mediation and moderation analyses.ResultsLMX, JE, and JS were significantly negatively correlated with Turnover Intention (TI) (r = –0.365, p < 0.01; r = –0.571, p < 0.01; r = –0.517, p < 0.01). JS fully mediated the link between LMX and TI (ab = –0.384, 95%CI: [–0.497, –0.285]) and partially mediated the link between JE and TI (ab = –0.237, 95%CI: [–0.350, –0.123]). CS significantly moderates these relationships: positive CS enhanced employees’ JE and JS, while negative CS weakened organizational commitment and increased turnover likelihood.DiscussionCS can temporarily intensify the relationships between LMX, JE, JS, and TI under certain circumstances, likely due to heightened employee sensitivity to leadership support, work environment, and career development. This moderation effect also highlights that employees’ demand for organizational support increases when facing career challenges, and high-quality LMX and JE can provide essential assistance for employees to navigate career shocks.ConclusionBy investigating the impact of LMX, JE, JS, and CS on turnover intention, this study offers a fresh perspective on the occupational behavior of medical staff in public hospitals. The findings not only enrich LMX and career shocks theories but also provide practical guidance for managers. This guidance empowers managers to reduce employee turnover intention, making them feel capable and ready to implement these strategies. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require one – please see the “Article types” on every Frontiers journal page for full details.